2016
DOI: 10.1002/prp2.216
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological comparison of a nonhuman primate and a rat model of oxaliplatin‐induced neuropathic cold hypersensitivity

Abstract: Oxaliplatin is a first‐line treatment for colorectal cancer. However, shortly following treatment, cold‐evoked hypersensitivity appears in the extremities and over time, the pain is such that oxaliplatin dosing may need to be markedly reduced or even terminated. There is currently a lack of efficacious treatments for oxaliplatin‐induced peripheral neuropathy, which is due in part to the difficulty in translating findings obtained from preclinical rodent models of chemotherapy‐induced peripheral neuropathy. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…214,229 In theory, an NHP-model might be an improvement over widely used rodent models, but the use of NHPs has been challenged on ethical and scientific grounds. 230 A viable and rapidly developing approach is to use a model that avoids the use of non-human tissues and which instead incorporates sensory neurons derived from human stem cells.…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
“…214,229 In theory, an NHP-model might be an improvement over widely used rodent models, but the use of NHPs has been challenged on ethical and scientific grounds. 230 A viable and rapidly developing approach is to use a model that avoids the use of non-human tissues and which instead incorporates sensory neurons derived from human stem cells.…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
“…There were three duloxetine treatment groups with different doses of duloxetine: 10 mg/kg [P+D (L)], 20 mg/kg [P+D (M)] and 30 mg/kg [P+D (H)] (Toyama et al, 2017;Shidahara et al, 2016). Duloxetine was injected i.p.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Oxaliplatin treatment in cynomolgus macaques leads to a significant hypersensitivity to 10°C cold, beginning three days after intravenous oxaliplatin infusion (two-hour i.v. infusion 5 mg/kg; human equivalent dose of 1.6 mg/kg [ 13 , 43 ]) ( Figure 1 ). Furthermore, treatment with the serotonergic-norepinephrine reuptake inhibitor duloxetine (p.o.…”
Section: A Nonhuman Primate Model Of Oxaliplatin-induced Neuropathmentioning
confidence: 99%
“…30 mg/kg) did not alter cold hypersensitivity ( Figure 1 ). The lack of efficacy of pregabalin and tramadol in the macaque model contrasts with robust efficacy observed in rodent models of oxaliplatin-induced neuropathic pain [ 33 , 43 45 ]. The limited macaque pharmacological data parallel findings from randomized, placebo-controlled clinical trials, in that duloxetine showed significant efficacy in chemotherapy-induced peripheral neuropathic pain [ 46 ], whereas pregabalin did not [ 47 ].…”
Section: A Nonhuman Primate Model Of Oxaliplatin-induced Neuropathmentioning
confidence: 99%